2009
DOI: 10.1038/gene.2009.3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the interleukin 3 gene show strong association with susceptibility to Graves’ disease in Chinese population

Abstract: Graves' disease (GD) is a common organ-specific autoimmune disorder, which is multifactorial and develops in genetically susceptible individuals. We had earlier mapped a susceptibility locus for GD to chromosome 5q31-33 in a linkage study. Here we used tag single-nucleotide polymorphisms (SNPs) to search for genetic variants associated with GD, and examined 19 functional candidate genes in this chromosomal region. We identified 192 polymorphisms by re-sequencing the candidate genes, and selected 51 tagSNPs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…For instance, Chu reported that a non-synonymous single-nucleotide polymorphism rs40401 (P27S) of the interleukin 3 ( IL3 ) gene was associated with increased risk of GD [36]; Guo found the rs568408 polymorphism in the interleukin-12 ( IL-12 ) gene was also associated with increased risk of GD [37]. In addition, polymorphisms in the ADRB2 gene [3], interleukin-10 ( IL-10 ) gene [38], TNF-α gene [39] were also found to be associated with GD in Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Chu reported that a non-synonymous single-nucleotide polymorphism rs40401 (P27S) of the interleukin 3 ( IL3 ) gene was associated with increased risk of GD [36]; Guo found the rs568408 polymorphism in the interleukin-12 ( IL-12 ) gene was also associated with increased risk of GD [37]. In addition, polymorphisms in the ADRB2 gene [3], interleukin-10 ( IL-10 ) gene [38], TNF-α gene [39] were also found to be associated with GD in Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Among the above-mentioned loci, the most promising results have been obtained for marker rs40401 and its perfect proxy single nucleotide polymorphism (SNP) rs31480 (both located in the IL-3 gene), whose association with GD was found in three independent Chinese population samples (Chu et al 2009a;Zhu et al 2010). Association between marker rs31480 of IL-3 and GD was not confirmed in a recent well-powered study of British Caucasians (Simmonds et al 2010).…”
Section: Introductionmentioning
confidence: 93%
“…To explain the association of the region 5q31-33 with Graves' disease (GD), an autoimmune hyperthyroidism, several positional candidates were considered, including interleukin 3 (IL-3) (Chu et al 2009a;Zhu et al 2010), IL-4 (Heward et al 2001;Nakkuntod et al 2004;Yang et al 2005), IL-5 (Zhu et al 2010), IL-9 (Zhu et al 2010), IL-12B (Ikeda et al 2004), IL-13 (Yang et al 2005;Chong et al 2008;Zhu et al 2010), beta-2-adrenergic receptor (ADRB2) (Jazdzewski et al 2007;Chu et al 2009b), and interferon regulatory factor 1 (IRF1) (Yang et al 2005). The association analyses showed inconsistent results, likely due to the lack of genetic power because most of the population studies had a small sample size not exceeding a total of 1,000 cases and controls.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, out of these, variants in IL3 [170,171], IL5 [171] and ADRB2 [172,173] were all associated with GD. …”
Section: Genes Predisposing To Gdmentioning
confidence: 99%